Prolonged pudendal nerve terminal motor latency is associated with decreased resting and squeeze pressures in the intact anal sphincter. (November 2013) - Loganathan, A.; Schloithe, A. C.; Hakendorf, P.; Liyanage, C. M.; Costa, M.; Wattchow, D.
Abstract Aim To determine the contribution of the pudendal nerve to the anal continence mechanism by determining the correlation between pudendal nerve terminal motor latency (PNTML) and resting and squeeze anal canal pressures. Method In all, 1051 patients were investigated with anorectal physiology studies between January 1998 and July 2010. Of these, 213 patients had intact anal sphincters on endoanal ultrasound and had undergone PNTML testing and anal manometry with measurement of resting and squeeze pressures. The relationship between PNTML and mean resting and squeeze pressures was compared in these patients with an intact anal sphincter. Values were compared using a two‐sample t test with equal variances. A P value of < 0.05 was considered significant. Results Of these patients 40.8% had normal PNTML bilaterally, 9.9% had slow PNTML bilaterally and 21.6% had a unilateral slow PNTML. Mean resting pressure was significantly reduced in patients with unilateral slow and bilateral slow PNTML compared with normal. The magnitude of the reduction was 28% and 19% respectively. Mean squeeze pressure was significantly reduced in patients with unilateral slow and bilateral slow PNTML compared with normal. The magnitude of the reduction was 18% and 23% respectively. Conclusion In patients with an intact anal sphincter, either unilaterally or bilaterally prolonged PNTMLs are associated with significantly decreased resting and squeeze pressures. Our results suggest that both internal and external sphincter function is impaired with pudendal nerve injury. The inhibition of internal sphincter function may be due to damage of autonomic, principally sympathetic fibres carried in the pudendal nerve.